FAKTOR - FAKTOR YANG MENYEBABKAN HIPERTENSI DI KELURAHAN MEDAN TENGGARA - Delfriana Ayu A; Addina Fitri Sinaga; Nabila Syahlan; Siti Maharani Siregar; Shakila Sofi; Rahmad Siddiq Zega; Annisa Annisa; Tengku Anisa Dila (Jurnal Kesehatan Masyarakat (Undip), 2022)
Lately, hypertension is still the biggest challenge in Indonesia. How not, hypertension is a condition that is often found in primary health care. This is a health problem with a high prevalence of 25.8%. This study aims to determine the factors that cause hypertension in the kelurahan of Medan Tenggara in 2021. This research method uses quantitative research methods, with a cross sectional study approach. Samples were taken for respondent data using the Slovin formula (1960), and the number of samples obtained was 98 families (family cards). The process of collecting data by looking at medical records recorded in 2020 and 2021 and conducting field observations to 11 neighborhoods in the Southeast Medan village by distributing questionnaires to the public. In conclusion, the factors that cause hypertension in the Medan Tenggara sub-district are tobacco use behavior (smoking), fruit and vegetable consumption behavior, risky foods, flour processed foods and a history of other diseases. Based on the results of the data from the research conducted, it can be concluded that the majority of the highest age affected by hypertension are from the 41-50 year age category occupying the highest number in the Southeast Medan sub-district, namely 28 respondents (28.5%), with the distribution of tobacco use (smoking) ) (23.5%), with the distribution of consuming salty foods (34.7%), sweet foods (67.3%), fatty (39.8%), preservatives (17.3%) and seasonings. (49.0%) and consume instant noodles (29.6%).